Le travail … c’est la santé : la santé au travail … une pratique en question - Paul Frimat (Perspectives Interdisciplinaires sur le Travail et la Santé)
It was in 1946 that this new original institution, occupational medicine, was created in France. At the beginning, based mainly on an essentially individual approach, the concept of medical ability held a central place in the health system. This system has changed and the individual approach is now paired with a more collective vision, leaving the system still largely perfectible. Among these evolutions, the medical ability decision has become increasingly complex. Numerous reports have been written in the last five years to debate the legitimacy of maintaining such a concept, as well as its efficiency as far as the prevention of work-related pathologies is concerned. A law will certainly be expected at the end of 2009/beginning of 2010. But, what about practices ? What reality will remain ? Medical ability or disability… How can we help in the compatibility between the right to health and the right to work ? How has this French system, based on medical ability or disability, been able to offer guaranties to employers, workers, society ? That is the purpose of this presentation.